2008
DOI: 10.1002/ejoc.200800080
|View full text |Cite
|
Sign up to set email alerts
|

Anthraquinones as Artificial DNA Building Blocks

Abstract: Synthesis and properties of oligodeoxynucleotides containing anthraquinone-derived building blocks with flexible linkers are described. Starting from the 1,4-, 1,5-, 1,8-and 2,6-dihydroxyanthraquinone isomers, the corresponding phosphoramidites were prepared and incorporated into oligonucleotides. The site of linker attachment was found to be of critical importance for hybrid stability. Whereas the 2,6-iso-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 72 publications
0
8
0
Order By: Relevance
“…4g). 90 S he DNA bases was analysed and confirmed crystallographically. 91 Among the various chromophore inserted, those which showed distinct photophysical properties arising from their position in the DNA duplex were of the greatest interest.…”
Section: Dna/chromophore Precision Oligomersmentioning
confidence: 99%
“…4g). 90 S he DNA bases was analysed and confirmed crystallographically. 91 Among the various chromophore inserted, those which showed distinct photophysical properties arising from their position in the DNA duplex were of the greatest interest.…”
Section: Dna/chromophore Precision Oligomersmentioning
confidence: 99%
“…[329][330][331] Anthraquinone has been used as an artificial base in duplex DNA, and it was found that the site of linker attachment was critical for duplex stability with only the 2,6-isomer (77) stabilising duplex DNA. 332 The imidazole nucleoside (78) has been introduced into triplexforming oligonucleotides, where it forms a stable partner with a CG base pair. 333 The LNA analogues (27) and (28) also have use in TFOs, where they can stabilise a triplex even at a T:A interruption site.…”
Section: Oligonucleotides Containing Modified Sugarsmentioning
confidence: 99%
“…They prepared clusters of phenanthrene, 54,55 pyrene, 56-59 perylenediimide 60,61 and anthraquinone. 62 Recently, they reported that oligopyrenotides, in which pyrene moieties are tethered without natural nucleobases, could form their hybrids in aqueous solution. 63 Wagenknecht and co-workers utilized (S)-1-aminopropane-2,3-diol as a linker and prepared clusters of various kinds of fluorophores.…”
Section: Hiroyuki Asanumamentioning
confidence: 99%